Upaya Meningkatkan Kesadaran Menerapkan K3 (keselamatan dan kesehatan kerja) pada Pelajaran Produktif dengan Pendekatan Pembelajaran Experiential Learning Cycle (ELC) Kelas X Teknik Las SMK Negeri 2 Karang Baru - Mustafa (Multiverse: Open Multidisciplinary Journal, 2022)
This Classroom Action Research (CAR) was carried out considering how important it is to improve the quality of learning outcomes through various ways or optimal learning strategies, where teachers play a very important role in preparing students to take part in learning. This Experiential Learning Cycle (ELC) learning approach method, namely: understanding, relevant methods, and implementation of the ELC learning approach in Class X Students of Welding Engineering SMK Negeri 2 Karang Baru. It is felt that it is very necessary to apply OSH in the workshop environment and other practice places, because the interest and motivation as well as the learning outcomes of students in these classes are still low. The subjects of this study amounted to 20 people. The research data was obtained by using a performance test in the form of an introduction to K3 tools and student observation sheets. From the results of this study it was revealed that students' ability/concern about OSH in using interactive learning methods could be improved. The average score of student learning outcomes from cycle I and cycle II continued to increase (from 81.75 to 87.90) with the category of students completing cycle I (65%) and cycle II (100%).